Making Connections : A Teaching Strategy To Foster Junior High School Students’ Reading Comprehension - Ariana Ariana; Ardiana Ardiana (Universitas Cokroaminoto Palopo, 2021)
Reading is the process of looking at a series of written symbols and getting meaning from them. When we ready, we use our eyes to receive written symbols (letters, punctuation mark and spaces) and we use our brain to convert them into words, sentences and paragraphs that communicate something to us. According to Spedell (2015), good readers make connections as they read. They can relate the book to their personal experiences (text-to-self), to information from other texts (text-to-text), or from what they know about the world (text-to-world). Making connections was linking what the students read, to what they already know. This strategy helped students comprehend text, by activating their prior knowledge and making meaning of what they read. This research aimed at finding out the improvement of students in reading comprehension through making connections strategy to eleventh grade students of SMP N 3 Galesong Utara which refers to the familiarity of subject matter of the narrative text in terms of literal comprehension covering main idea and supporting details. The researcher applied pre-experimental design and VIII A class consist of 18 students with 5 men and 13 women as a research subject. The Result of this research was in main idea, the students’ mean score achievement in pre-test was 42.78 becomes 65.83. So, the improvement of students’ reading comprehension achievement from pre-test to post-test was 53.88%. In supporting details, the students’ mean score achievement in pre-test was 31.39, becomes 44.17. So the improvement of students’ reading comprehension achievement from pre-test to post-test was 40, 71%. And the mean score of students’ reading comprehension in main idea and supporting details in pre-test 37.08 becomes 55. So the improvement of students’ reading comprehension achievement from pre-test to post-test was 48.33%